Influence of perceived parenting styles on students' career maturity - Chan, Christine (2014)
In Malaysia, along with the academic performance, career decision making is one of the most crucial decisions an adolescent must make especially when they need to make a choice to which stream of studies they are going to enroll. Many research have confirmed that adolescents with low level of career maturity will not be ready to make career decision as they will be easily affected by their significant others such as parents who are still the primary influence in affecting adolescents’ decision making. Little is known about the influence of parenting styles towards children career maturity in the perspective of Malaysian communities that comprise multi ethnicities such as Malay, Chinese and Indian that are staying in collectivist culture. Therefore, this study is conducted to bridge a gap in the current literature by exploring the influence of perceived parenting styles on career maturity of students. This study adopted correlation research design involving 228 Form Four students in Hulu Langat, Selangor who had been selected through proportionate random sampling. Career Maturity Inventory-Attitude Scale Screening Form A-2 (CMI-AS) was used to measure the level of career maturity while Parental Authority Questionnaire (PAQ) was used to measure the parenting style of parents as perceived by the Form Four students. This study reveals that ethnicity would not determine the types of parenting styles as one ethnicity practices different types of parenting styles. Besides, this study also found that the levels of career maturity were at the medium and high levels where respondents were ready to cope with the career developmental task. The results of T-Test indicated that there were no significant difference of career maturity between male and female students. Moreover, results from the Two-Way ANOVA analysis suggested that there were a significant interaction between the effects of ethnicity and parents’ parenting styles on students’ career maturity [F (2, 219) = 3.286, p = .012]. Results from the Pearson Correlation analysis showed that only authoritative parenting style and permissive parenting style were significantly correlated with career maturity. Results of this study have highlighted the importance of including parents and ethnicity variables when exploring career maturity of students. It is recommended that counsellors should involve parents in helping students to make career decisions, besides understanding the values hold by different cultures and religions. Other relevant variables and related samples are suggested to be included in future studies of students’ career maturity.